Digital Videos for the development of Computational Thinking in Basic Education (Revista BOEM, 2024)
The National Common Curricular Base (BNCC) highlights that it is essential to use more digital languages at school, more specifically in the teaching and learning of Mathematics. Among the possibilities, BNCC brings Computational Thinking (PC), a skill that is associated with the development of critical thinking and oriented towards solving problems that start from decomposition, pattern recognition, abstraction and creation of algorithms to solve these problems. This article aims to present the planning and development process of a set of Digital Educational Resources (RED) in the format of digital videos, which form the “PC-cratch” course, aiming to develop students' PCs by solving problems that involve First Degree Polynomial Function solved using Scratchsoftware. Furthermore, it seeks to present the results obtained in the application of the first RED to a 1st year high school class of the Technical Course Integrated to High School in Logistics at Escola Estadual Senador Levindo Coelho, located in the municipality of Ubá –MG. As a result of applying the first RED, a change was observed in the students' language about PC skills before and after using the RED. Regarding the RED planning and development process, we follow the Learning Object Methodology (MOA), where each production went through the five phases: analysis, design, implementation, review, submission/publication. Therefore, it is hoped that this article will serve as support for future researchers seeking work related to this topic, mainly in the development of RED.